FOOD PRICE VOLATILITY AND GENDER ROLE TRANSFORMATION: ECONOMIC PRESSURE AND HOUSEHOLD ADAPTATION IN WEST NUSA TENGGARA PROVINCE, INDONESIA - AHMAD GAUTSUL ANAM (J-TEDA: Journal of Tabulation Economic Data, 2025)
This study examines the relationship between food price volatility and gender role transformation within households in West Nusa Tenggara Province during 2024. Using a mixed-methods approach that combines statistical analysis of food price data from the Central Bureau of Statistics with qualitative document analysis of family law frameworks, this research reveals that significant fluctuations in staple food prices particularly rice (Rp14,568-Rp16,666/kg), shallots (up to Rp41,736/kg), and beef (around Rp120,000/kg) have created substantial economic pressure on low to middle-income families. The findings demonstrate that economic stress has catalyzed a shift in traditional gender roles, with women increasingly participating in productive economic activities to supplement household income. From a legal perspective, this transformation represents a legitimate form of family cooperation (ta'awun) rather than a violation of traditional breadwinner responsibilities outlined in Marriage Law No. 1/1974 and the Compilation of Islamic Law. The study concludes that food price instability serves as a structural driver of gender role adaptation, necessitating policy interventions that protect dual-income households while maintaining family resilience.